2013
DOI: 10.1128/jvi.03155-12
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 9 in Plasmacytoid Dendritic Cells Fails To Detect Parvoviruses

Abstract: Toll-like receptor 9 (TLR9) recognizes genomes of double-stranded DNA (dsDNA) viruses in the endosome to stimulate plasmacytoid dendritic cells (pDCs). However, how and if viruses with single-stranded DNA (ssDNA) genomes are detected by pDCs remain unclear. Here we have shown that despite the ability of purified genomic DNA to stimulate TLR9 and despite the ability to enter TLR9 endosomes, ssDNA viruses of the Parvoviridae family failed to elicit an interferon (IFN) response in pDCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Although the biology for these different genera cannot be presumed to be identical, some similarities might nevertheless be expected. TLR-9 mediated an IFN response to wild-type AAV in murine and human pDCs (56), consistent with results for autonomous parvoviruses in hPBMCs (23) but in contrast to the absence of a response to MVMp seen by Mattei et al in murine pDCs (46). We found that exogenous IFN was unable to block infection of human cells by an AAV vector.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Although the biology for these different genera cannot be presumed to be identical, some similarities might nevertheless be expected. TLR-9 mediated an IFN response to wild-type AAV in murine and human pDCs (56), consistent with results for autonomous parvoviruses in hPBMCs (23) but in contrast to the absence of a response to MVMp seen by Mattei et al in murine pDCs (46). We found that exogenous IFN was unable to block infection of human cells by an AAV vector.…”
Section: Discussionsupporting
confidence: 71%
“…An absence of an IFN response to parvoviruses was reported in some murine cells, including A9 transformed murine fibroblasts (21) and murine plasmacytoid dendritic cells (46). Our study may be the first to investigate the IFN response to autonomous parvoviruses in a variety of normal human cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Lysosomal and cytoplasmic sensors binding viral RNA (TLR3, protein kinase R [PKR], RIG-I, and MAVS) or ssDNA (TLR9) sequences have been shown to respond to infection with the autonomous parvoviruses MVMp and H-1PV (36,44,(97)(98)(99)(100). Notably, the cell-type-dependent pattern of sensor expression determined both induction of the IFN response and permissiveness for virus infection, accounting for the abortion of the viral life cycle in TLR3/TLR9/PKR-positive fibroblasts or immune cells and for the success of virus replication in tumor cells lacking these intracellular receptors.…”
Section: Discussionmentioning
confidence: 99%